Formalization and Administrative Burden as Obstacles to Employee Recruitment: Consequences for the Public Sector. (March 2022) - Sievert, Martin; Vogel, Dominik; Feeney, Mary K.
Job advertisements are a crucial first step in the recruitment process. Public sector organizations overwhelmingly rely on passive recruitment tactics such as written notices, listing formal rules and legal processes, and excessive application procedures. Little is known about the signals these formal rules and procedures send to potential applicants. This research uses a survey experiment to examine the effects of formalization and administrative burden in public sector job advertisements on individuals' intention to apply for a job and the moderating role of public service motivation, person–organization fit, and person–job fit. The results indicate that formalization leads to lower application intentions. Administrative burdens such as compliance costs do not have a significant effect. These findings emphasize the negative signal of formalization in public sector job advertisements, which has the effect of making these jobs less desirable to potential applicants.